Design of TPACK Based PBL Student Worksheet to Enhance Creative Thinking Skills - Roudlotul Jannah; Utiya Azizah; Sukarmin Sukarmin; Suyono Suyono; Zainul Arifin Imam Supardi; Muhammad Satriawan (Journal of Natural Science and Integration, 2025)
This study aimed to develop a Problem-Based Learning (PBL) Student Worksheet (LKPD) based on the Technological, Pedagogical, and Content Knowledge (TPACK) framework to enhance students’ creative thinking skills in the topic of reaction rates. The designed LKPD is intended to provide a challenging and meaningful learning experience, fostering students’ critical and creative problem-solving abilities in the context of reaction rate concepts. The PBL approach facilitates active student engagement, while the TPACK framework ensures the integration of technology, pedagogy, and content knowledge in the learning process. The research employed the 4D development model, focusing on the Define, Design, and Develop (expert validation) stages. Data for the Define stage were collected from a Chemistry teacher and Grade XI students at SMA Ta’miriyah Surabaya to conduct a needs analysis. Descriptive qualitative analysis was applied to examine the needs analysis outcomes and the LKPD design blueprint. The results indicate that the developed LKPD possesses a clear structure and is highly relevant for fostering students’ creative thinking skills. Expert validators classified the LKPD as “Highly Valid.” In conclusion, the developed LKPD is feasible as a contextual learning resource and has strong potential to enhance students’ creative thinking skills in integrated science learning.Keywords: student worksheet, problem based learning, TPACK, creative thinking